2011
DOI: 10.1371/journal.pone.0026772
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Cross-Talks with JH Signaling by Suppressing Met and gce Expression

Abstract: Juvenile hormone (JH) plays key roles in controlling insect growth and metamorphosis. However, relatively little is known about the JH signaling pathways. Until recent years, increasing evidence has suggested that JH modulates the action of 20-hydroxyecdysone (20E) by regulating expression of broad (br), a 20E early response gene, through Met/Gce and Kr-h1. To identify other genes involved in JH signaling, we designed a novel Drosophila genetic screen to isolate mutations that derepress JH-mediated br suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…For example, the Wnt signaling pathway is involved in animal development. In Drosophila, it has been shown that Wnt signaling involves cross-talk with JH signaling by suppressing the transcription of genes that encode putative JH receptors [45]. This result further supports the role of MSG-A in silk gland development.…”
Section: Discussionsupporting
confidence: 63%
“…For example, the Wnt signaling pathway is involved in animal development. In Drosophila, it has been shown that Wnt signaling involves cross-talk with JH signaling by suppressing the transcription of genes that encode putative JH receptors [45]. This result further supports the role of MSG-A in silk gland development.…”
Section: Discussionsupporting
confidence: 63%
“…Approximately 90 cytochrome P450 genes exist in the Drosophila melanogaster genome 36 and are involved in hormone biosynthesis and metabolism, (e.g., insect juvenile hormone (JH)) 37 38 39 . JH plays an essential role in insect development, metamorphosis, and reproduction 40 41 . The heterosis for body weight may therefore be modulated by these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Insect metamorphosis is mediated by 20E and JH signals. During larval stage, JH exhibits its "status quo" function probably through two transcription factors, E75A and Kr-h1, to prevent the activation of BR-C , a 20E signal transduction gene for larvae-pupae transition [ 7 , 47 ]. Though a relative high titer of JH was present in hemolymph of B. mori at the end of the final instar larvae [ 48 ], the JH does not inhibit the wing disc transformation.…”
Section: Discussionmentioning
confidence: 99%